Compliance Analysis of Inventory Accounting Treatment at PT Rapid Niaga International: Alignment with PSAK No. 14 of 2018 - Mohammad Ali Wairooy; Rahmi (JEKAMI Journal of Accounting, 2025)
The objective of this research was to assess whether the recording, valuation, presentation, and disclosure of inventory at PT Rapid Niaga International complied with PSAK No. 14 of 2018. The study employed a Comparative Description Analysis method to evaluate the alignment of the company’s inventory accounting practices with the applicable financial reporting standards. The findings revealed that the valuation and presentation of inventory in the company’s financial reports adhered to PSAK No. 14 of 2018, indicating that PT Rapid Niaga International applied the appropriate inventory valuation methods and presented the inventory in accordance with the standard’s requirements. However, the research also identified that the company’s method of recording and disclosing inventory in its financial statements did not fully comply with PSAK No. 14 of 2018. This suggests potential inconsistencies in the application of inventory recognition principles or inadequate transparency in reporting inventory-related information. The non-compliance in recording and disclosure could lead to misinterpretations by stakeholders relying on the financial statements for decision-making. Therefore, improvements in these areas are necessary to enhance financial reporting accuracy and ensure full adherence to PSAK No. 14 of 2018. Implementing standardized recording practices and improving disclosure transparency could contribute to better financial accountability and reliability